2019
DOI: 10.1038/s41467-019-10834-5
|View full text |Cite
|
Sign up to set email alerts
|

Rearrangement of the transmembrane domain interfaces associated with the activation of a GPCR hetero-oligomer

Abstract: G protein-coupled receptors (GPCRs) can integrate extracellular signals via allosteric interactions within dimers and higher-order oligomers. However, the structural bases of these interactions remain unclear. Here, we use the GABA B receptor heterodimer as a model as it forms large complexes in the brain. It is subjected to genetic mutations mainly affecting transmembrane 6 (TM6) and involved in human diseases. By cross-linking, we identify the transmembrane interfaces involved in GABA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
39
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(48 citation statements)
references
References 70 publications
9
39
0
Order By: Relevance
“…2b, Fig. 3d), consistent with previous cross-linking studies 40 . This interface is also observed in the agonist-bound structure of the mGlu5 homodimer 33 , suggesting the TM6/TM6 interface is likely a hallmark of activation of class C GPCR.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…2b, Fig. 3d), consistent with previous cross-linking studies 40 . This interface is also observed in the agonist-bound structure of the mGlu5 homodimer 33 , suggesting the TM6/TM6 interface is likely a hallmark of activation of class C GPCR.…”
Section: Resultssupporting
confidence: 92%
“…2, Extended Data Fig. 7a, b), propagating through the stalk domains to the TM domains, which in turn reorients the TM interface between two subunits from TM3-TM5/TM3-TM5 in the inactive state to TM6/TM6 in the active state, in perfect agreement with previous crosslinking data for GABA B receptor and mGlu homodimers 40,46 . Therefore, the overall domain rearrangements upon activation of GABA B receptor resemble the published cryo-EM structures of mGlu5 33 , suggesting this reorientation of TM domains is possibly the hallmark of class C GPCR activation.…”
Section: Resultssupporting
confidence: 88%
“…Binding studies of isolated GABA B2 subunits and studies manipulating the receptor composition showed that the GABA B2 7TM domain is mainly responsible for recruiting G-proteins, in addition to hosting an allosteric binding site [23][24][25]. There is also evidence from biochemical and biophysical studies that the GABA B1 7TM participates in formation of GABA B -R oligomers by interacting with other GABA B1 7TMs in the inactive state [26][27][28]. The receptor was found to be in equilibrium between heterodimers and oligomers by applying SNAP-tag technology [27].…”
Section: Structure Of the Gaba B Receptormentioning
confidence: 99%
“…Changes in the 7TM subunit interaction interface upon agonist activation of the GABA B -R have been quantified by cysteine cross-linking studies [26], and is also described in the in the newly released papers describing cryo-EM structures [6,7]. The 7TM domain interface interactions in the inactive state is formed by TM3 (GABA B1 )-TM5 (GABA B2 ) and TM5 (GABA B1 )-TM3 (GABA B2 ) interactions and that the interactions between the protomers are facilitated through ionic interactions stabilized by aromatic residues [6,9,26]. The distance between the backbones of TM5 in each monomer is 8 Å and thereby much shorter than the distance between the homodimers in the inactive mGlu5, which is 21 Å [6,44].…”
Section: Transmembrane Domainsmentioning
confidence: 99%
“…Systems investigated via disulfide trapping include ligand-bound class B GPCRs [ 93 , 94 , 95 ], chemokine receptors [ 96 , 97 ], the M3 muscarinic acetylcholine receptor [ 98 , 99 , 100 ], and other receptors [ 101 , 102 ]. Disulfide trapping has been used also to study GPCR dimerization [ 103 , 104 , 105 , 106 ] and to characterize interaction interfaces between GPCRs and G protein or arrestin [ 107 ]. Unfortunately, disulfide trapping does not always yield clear results, probably because of the requirement of nonreducing conditions during analysis of samples [ 93 , 95 , 96 , 98 ].…”
Section: The Contact Interfacementioning
confidence: 99%